Can caesarean section be ‘natural’? The hybrid nature of the nature-culture dichotomy in mainstream obstetric culture - Maffi, Irene (Tidsskrift for Forskning i Sygdom og Samfund, 2013)
Reflecting on the recent creation of the surgical technique of ‘natural caesarean’, this paper investigates how caesarean section, a major abdominal surgery, can be associated with ‘natural childbirth’ To understand the paradoxical creation of this concept, I look back at the history of obstetrics and at the evolution of the nature/culture dichotomy in European modern thought. The multiple meanings of these two concepts and the epistemological and social premises underpinning the formation of modern obstetrics are examined to unravel the complexity of current medical practices applied to women’s bodies as well as women’s attitudes. In light of these historical elements, natural caesarean is understood as a notion born from cultural and professional negotiations and fraught with contradictory meanings originating from different medical and cultural discursive traditions.